MORPHOTYPIC VARIABILITY IN THE DENTITION OF STENOCRANIUS GREGALIS PALLAS (RODENTIA, MAMMALIA) FROM THE PLEISTOCENE OF DENISOVA CAVE - Serdyuk N.V. (My University, 2001)
The morphological variability of Stenocranius gregalis Pallas from the Paleolithic site Denisova Cave (Altai) is examined. The variability of the unpaired anterior loop of M] is discussed. Seven morphological types are distinguished. Based on the morphometric analysis, the beds of the Denisova Cave are dated as the Upper Pleistocene.
Keywords: Pleistocene; Stenocranius gregalis; Denisova Cave; Altai; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен